Measured as poor versus feeling poor: Comparing objective and subjective poverty rates in South Africa - Dorrit Posel; Michael Rogan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
In this paper, we compare subjective and money-metric measures of poverty in South Africa using data collected in the 2008/09 Living Conditions Survey. In addition to collecting detailed information on expenditure, the survey asked respondents to provide an assessment of the economic status of their household, ranging from 'very poor' to 'wealthy'. We find considerable overlap between per capita expenditure measures of poverty status and subjective poverty status among households. However, we also identify a number of significant characteristics which distinguish households where poverty measures do not overlap. These characteristics highlight not only low dimensionality in expenditure measures of economic status, but also the likely underestimation of economic resources in the household. This underestimation arises both because poverty measures based on per capita expenditure do not recognize scale economies in the household, and because the value of economic activity can be difficult to measure, as in the case of subsistence farming.
Keywords: I32; O12; 330; income poverty; subjective poverty; economies of scale; adult equivalence